Creative skills in solving environmental problems among kindergarten children (Journal of the College of Education for Women, 2019)
Acquires this research importance of addressing the subject (environmental problems) withage group task, a category that children pre-school, and also reflected the importance ofresearch, because the (environmental problems) constitute a major threat to the continuationof human life, particularly the children, so the environment is Bmchkladtha withinkindergarten programs represent the basis of a hub of learning where the axis, where thekindergarten took into account included in the programs in order to help the development ofenvironmental awareness among children and get them used to the sound practices andbehaviors since childhood .The research also detected problem-solving skills creative with kids Riyadh, and because therelationship between the skills of creativity and problem-solving environmental starts alwaysa sense of the problem and clear the roots of creativity in the awareness that there is adeficiency or obscure what needs to be solved, and thus became the style of solving theproblem demand basis for learning as the child is facing in their daily lives much of theproblems that require the use of methods to solve educated to confront them and the style ofthe creative solution to problems through the Provisions of creative skills (originality,flexibility, fluency and sensitivity to the problems).This prompted the researcher to do a field study, addressed the (environmental problems) onthe children of Riyadh, this segment of society, certainly it feels too much suffering, butbecause of their young age, they can not deliver their voices to others, because most of theadults around them may not meet the needs and demands of helping get rid of them, this felt aresearcher at the meet the needs of these children through the construction of a test based onthe creative skills of the solution to environmental problems with this category .oahdf thissearch